A Regulatory Network Controls cabABC Expression Leading to Biofilm and Rugose Colony Development in Vibrio vulnificus - Hwang, Seung-Ho; Park, Jin Hwan; Lee, Byungho; Choi, Sang Ho (Frontiers in Microbiology, 2020)
Biofilms provide bacteria with protection from environmental stresses and host immune defenses. The pathogenic marine bacterium Vibrio vulnificus forms biofilms and colonizes environmental niches such as oysters. The cabABC operon encodes an extracellular matrix protein CabA and the corresponding type I secretion system, which are essential for biofilm and rugose colony development of V. vulnificus. In this study, molecular biological analyses revealed the roles of three transcriptional regulators BrpR, BrpT, and BrpS in the regulatory pathway for the cabABC operon. BrpR induces brpT and BrpT in turn activates the cabABC operon in a sequential cascade, contributing to development of robust biofilm structures. BrpT also activates brpS, but BrpS represses brpT, constituting a negative feedback loop that stabilizes brpT expression. BrpT and BrpS directly bind to specific sequences upstream of cabA, and they constitute a feedforward loop in which BrpT induces brpS and together with BrpS activates cabABC, leading to precise regulation of cabABC expression. Accordingly, BrpS as well as BrpT plays a crucial role in complete development of rugose colonies. This elaborate network of three transcriptional regulators BrpR, BrpT, and BrpS thus tightly controls cabABC regulation, and contributes to successful development of robust biofilms and rugose colonies in V. vulnificus.